2018
DOI: 10.1159/000489900
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Implementation of Pathogen Inactivation for All Platelet Concentrates in Switzerland

Abstract: Introduction: Bacterial contamination of platelet concentrates (PCs) has been identified as the most prevalent transfusion-associated infectious risk. To prevent PC-related septic transfusion reactions, the Intercept® pathogen inactivation procedure was introduced for all PCs in Switzerland in 2011. Methods: Based on numbers of transfused units and mandatorily reported adverse events with high imputability, we compare the risks associated with transfusion of conventional PCs (cPCs) and pathogen-inactivated PCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…Since 2008, the reduced PC storage time led to a reduction in reported transfusion incidents by approximately 50% in comparison to the period before introduction of this measure, thus, resulting in a total of 5.3 cases per 10 6 platelet units. Interestingly, however, the analysis of hemovigilance data from 2005 to 2010 in Switzerland documented that the frequency of transfusion-transmitted bacterial infections was almost equally distributed among PC stored for 5 or 4 days [28]. Thus, prevention of 50% of TTID might represent the maximum benefit to be expected from PC storage time reduction to 4 days.…”
Section: Risk Mitigation Through Platelet Storage Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2008, the reduced PC storage time led to a reduction in reported transfusion incidents by approximately 50% in comparison to the period before introduction of this measure, thus, resulting in a total of 5.3 cases per 10 6 platelet units. Interestingly, however, the analysis of hemovigilance data from 2005 to 2010 in Switzerland documented that the frequency of transfusion-transmitted bacterial infections was almost equally distributed among PC stored for 5 or 4 days [28]. Thus, prevention of 50% of TTID might represent the maximum benefit to be expected from PC storage time reduction to 4 days.…”
Section: Risk Mitigation Through Platelet Storage Limitationmentioning
confidence: 99%
“…A similar situation is found in Switzerland, where the Intercept system was generally introduced in 2011. Recently, Jutzi et al [28] assessed the implementation of PR by comparing the number of reported adverse reactions related to both traditional and PR-treated PC. Before PR implementation, 2–4 septic reactions per year or 125 adverse reactions per million platelets units were reported.…”
Section: Elimination Of Bacterial Contaminations Using Pathogen Reducmentioning
confidence: 99%
“…Collectively, these have proven very effective in reducing the rates of bacterial contamination and associated septic transfusions reactions by 50 to 75% . Nonetheless, the residual contamination risk is approximately 1 in 10 000 transfused PCs with nonfatal reactions occurring in 1 in 100 000 and fatal reactions in 1 in 500 000 transfused PCs, respectively, further action is needed .…”
Section: Concepts Of Microbial Safetymentioning
confidence: 99%
“…In 2014 several papers considered the influence of blood product characteristics or modifications on product safety and transfusion efficacy [2][3][4][5][6]. The current issue deals with the nationwide implementation of pathogen inactivation (PI) for all platelet concentrates (PC) in Switzerland, as presented by Markus Jutzi and colleagues [7]. One of their major aims was to eliminate bacterial infections due to PC transfusion.…”
mentioning
confidence: 99%
“…One of their major aims was to eliminate bacterial infections due to PC transfusion. Jutzi et al [7] reported that PI was successful to reduce the PC bacterial infection rate in Switzerland since 2011 to zero. The focus of this issue, however, is the interaction between the Rhesus blood group system and the recipients of red blood cell (RBC) components and/or PC [8][9][10][11].…”
mentioning
confidence: 99%